[PP.14.04] AN INTEGRATED APPROACH OF PHARMACIES AND GENERAL PRACTICES FOR DETECTION OF UNDIAGNOSED ATRIAL FIBRILLATION IN THE ISOLA D'ELBA: THE ELBA-FA STUDY. (September 2017) - Modesti, P.A.; Donigaglia, G.; Fabiani, P.
Abstract : Objective: Data available for Italy indicate that prevalence of atrial fibrillation (AF) among subjects aged 65 years or more is markedly lower in observational studies based on the diagnosis recorded by general practitioners (5–6%) than in studies where ECG screening was routinely offered to the general population (10–11%). New approaches are thus required to increase early detection of this arrhythmia at population level. This study aims to determine the feasibility and impact of a combined screening program for detection of previously undiagnosed AF in a confined area of Italy (Isola d'Elba) with the participation of pharmacies and general practices. Design and method: Isle of Elba, the third largest Isle of Italy (223 km 2 ), has a population of about 33000 inhabitants, with about 8000 subjects aged 65 years or more. ECG screening (MyDiagnostick, handheld single-lead ECG) will be offered to people aged 65 years or more in 10 community pharmacies and 10 general practices targeting a total of 1000 participants. Test will be performed by the pharmacist on duty or the general practitioner, with a cardiology consultation centre at the Hospital of the Isle (Portoferraio). Patients with newly detected AF will be referred to their GP for appropriate clinical management. Results: Primary outcome is the proportion of patients identified with undiagnosed AF. Secondary outcomes are new cases of atrial fibrillation detected within the 12-month study period; the level of agreement for identification of AF between the automated algorithm and the cardiologist; the proportion of participants that remain in AF, from the positive diagnosis at the screening phase (MyDiagnostick) to the 12-lead ECG performed during the cardiology review (paroxystic AF); incremental cost per case detected; cost-effectiveness of screening in Italy; community prevalence and incidence of AF; acceptability of AF screening and patient uptake; estimation of stroke risk of the participants identified with AF (using CHA2DS2-VASc score); reduced incidence of stroke at Isola d'Elba among subjects aged more than 65 years (historical comparison). Conclusions: The findings of this study will have broad implications for the general population with undiagnosed AF.